Father trait anger: Associations with father–infant bonding and subsequent parenting stress - Francis, Lauren M.; Youssef, George J.; Greenwood, Christopher J.; Enticott, Peter G.; Curtis, Ashlee; Graeme, Liam G.; Mansour, Kayla A.; Olsson, Craig A.; Skouteris, Helen; Milgrom, Jeannette; Williams, Joanne; Knight, Tess; et al. (Frontiers in Psychology, 2023)
Parent anger presents a risk to family safety and child development. Father trait anger may also compromise the early relational context of fathers and offspring, yet evidence is lacking. The aim of this study is to examine effects of father trait anger on parenting stress in the toddler years, and the mediational role of father-infant bonding. Data were from 177 Australian fathers of 205 children. Trait anger (total, angry temperament, and angry reaction), father-infant bonding subscales (patience and tolerance, affection and pride, and pleasure in interaction), and subsequent parenting stress (parental distress, difficult child, and parent-child dysfunctional interaction) were assessed. At each of the subscale levels, mediational path models examined whether father-infant bonding explained the relationship between trait anger and parenting stress. Models were presented where there was at least a small association between the mediator and both the predictor and outcome. Patience and tolerance was the only domain of father-infant bonding correlated with both trait anger and all parenting stress outcomes. Patience and tolerance partially mediated the effect of total trait anger on parental distress and fully mediated effects on difficult child and parent-child dysfunctional interaction. Patience and tolerance fully mediated relationships between angry temperament and all domains of parenting stress. Angry reactions only had a direct effect on parental distress. In conclusion, father trait anger both directly and indirectly (through patience and tolerance in the father-infant bond) impacts their experiences of parenting stress in the toddler years. Early interventions to manage father trait anger and improve father-infant bonding may benefit fathers and children.